2018
DOI: 10.18203/issn.2454-5929.ijohns20180713
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing difficulties among healthy elderly: prevalence and aetiology

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Dysphagia is a common problem among elderly individuals. Very few studies have been done to know the prevalence of dysphagia among healthy elderly individuals. So a study was done to assess the prevalence of swallowing difficulties among healthy elderly individuals and to find out the various causes for it in them. </span></p><p class="abstract"><strong>Methods:</strong> <span lang="EN-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Further, Roy et al 13 found 37.6% of community living elder had swallowing problems during their lifetime. The lower prevalence in our study than previous studies, 8 , 9 , 12 , 14 , 15 may have been due to elders who had chronic disease such as stroke or cancer being excluded from our this study. The average age in this study was also lower than in other studies, and the swallowing screening tool for each study was different.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Further, Roy et al 13 found 37.6% of community living elder had swallowing problems during their lifetime. The lower prevalence in our study than previous studies, 8 , 9 , 12 , 14 , 15 may have been due to elders who had chronic disease such as stroke or cancer being excluded from our this study. The average age in this study was also lower than in other studies, and the swallowing screening tool for each study was different.…”
Section: Discussioncontrasting
confidence: 68%
“…However, there was no correlation between gender and dysphagia in the present study, similar to the study of Abdul Khader and Mubeena. 15 …”
Section: Discussionmentioning
confidence: 99%
“…181 Of the 32 included studies, none of them recruited a nationally-representative 182 sample, twelve studies were from Europe and North America [34][35][36][37][38][39][40][41][42][43][44][45] seventeen from Asia 183 [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] two from Oceania [63,64] and one from South America [65]. Two studies recruited 184 participants aged 80 years or older [34,41], reporting too high prevalences of dysphagia to 185 be representative for the purpose of the present study.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%